Pengembangan Olahan Daun Kelor Sebagai Potensi Pendapatan Keluarga Di Desa Loru Kecamatan Sigi Biromaru Kabupaten Sigi - Gugun Mangesa; Harnida Wahyuni Adda; Betty Betty (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
This study aims to determine internal factors (Strenghts, Weaknesses) and external factors (Opportunities- Threats) in supporting the business deveopment of processed moringa leaf products in Loru Village. The detremination of the respondents was determined purposively (purposive). The number of respondents 6 consisted of 1 group leader and 2 group members,while external party respondents consisted of 3 consumers. The analysis used in the study is descriptive analysis and SWOT analysis. The results of the SWOT analysis show that the business development of processed moringa leaf products in Loru village is in the ST strategy, namely quadrant II,where in this posiyion overcoming existing threats by using the strengths of alternative strategies namely (1) Maximizing the use of capital in purchasing raw materials, (2) Maintaining a distinctive taste to anticipate changes in consumer tastes and face compotition with similar busisnesses, (3) Utilizing attractive product packaging and original taste in order to anticipate product equality substitution.